Acute‐on‐Chronic Liver Failure: Getting Ready for Prime Time?. Issue 4 (22nd September 2018) - Bajaj, Jasmohan S.; Moreau, Richard; Kamath, Patrick S; Vargas, Hugo E.; Arroyo, Vicente; Reddy, K. Rajender; Szabo, Gyongyi; Tandon, Puneeta; Olson, Jody; Karvellas, Constantine; Gustot, Thierry; Lai, Jennifer C.; et al.
Abstract : Acute on chronic liver failure (ACLF) is the culmination of chronic liver disease and extrahepatic organ failures, which is associated with a high short‐term mortality and immense health care expenditure. There are varying definitions for organ failures and ACLF in Europe, North America, and Asia. These differing definitions need to be reconciled to enhance progress in the field. The pathogenesis of ACLF is multifactorial and related to interactions between the immunoinflammatory system, microbiota, and the various precipitating factors. Individual organ failures related to the kidney, brain, lungs, and circulation have cumulative adverse effects on mortality and are often complicated or precipitated by infections. Strategies to prevent and rapidly treat these organ failures are paramount in improving survival. With the aging population and paucity of organs for liver transplant, the prognosis of ACLF patients is poor, highlighting the need for novel therapeutic strategies. The role of liver transplant in ACLF is evolving and needs further investigation across large consortia. A role for early palliative care and management of frailty as approaches to alleviate disease burden and improve patient‐reported outcomes is being increasingly recognized. Conclusion : ACLF is a clinically relevant syndrome that is epidemic worldwide and requires a dedicated multinational approach focused on prognostication and management; investigations are underway worldwide to prepare ACLF for prime time. (Hepatology 2018; 00:000‐000)